Odpowiedzialność karna za usiłowanie. Próba nowego spojrzenia - Wantoła, Michał (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The presented analyses are an attempt at a new look at the problem of criminal liability for attempt. The indicated legal institution evolved along with the development of criminal law, and the views on it changed along with the change of the general view on the functions associated with assigning criminal liability. In modern societies, there seems to be a tendency to extend criminal liability to the foreground of violating the legal good, in particular, to extend criminal liability for attempt or preparation. The question naturally arises as to what extent this process is needed and justified, and to what extent it raises concerns about its further development. Will it lead to an extension of the punishability of preparation? Can the ancient maxim “cogitationis poenam nemo patitur” lose its undisputed status in the name of the security of individuals, societies, and states? It must not be forgotten that the described tendencies may be strengthened in the face of the development of neurobiology, which can help in recognizing specific individuals as capable of committing a specific type of crime due to, for example, the occurrence of a specific gene or qualifying people as psychopaths or future recidivists.